2022
DOI: 10.1097/md.0000000000030960
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dynamic quadripolar radiofrequency on genitourinary atrophy and sexual satisfaction: A systematic review and meta-analysis

Abstract: Background: Physiologic processes such as childbirth and menopause can alter vulvovaginal aesthetic appearance, reduce sexual satisfaction, and cause symptoms of vulvovaginal atrophy which affects a woman’s quality of life. There is debate about whether dynamic quadripolar radiofrequency (DQRF) can be used to improve such conditions. We conducted a meta-analysis of studies among patients undergoing treatment with DQRF. Methods: We conducted a literature search without language or article type restriction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…RF treatments have been gaining popularity in the treatment of vaginal laxity due to the downtime and risk involved when compared to surgical procedures [ 31 ], offering an alternative for women who may not wish to undergo invasive surgical procedures [ 32 ]. In this study, after five times of RF therapy (monopolar mode for 15 min, bipolar mode for another 10-minute), 69.61% patients showed improvement in vaginal laxity according to VLQ score at 12 month and 29.41% patients obtained FSFI score no less than 26.55 at 12 months, accompanying by the elevated SSQ score, indicating temperature controlled dual-mode (monopolar and bipolar) RF contributed to the alleviated vaginal laxity and increased sexual satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…RF treatments have been gaining popularity in the treatment of vaginal laxity due to the downtime and risk involved when compared to surgical procedures [ 31 ], offering an alternative for women who may not wish to undergo invasive surgical procedures [ 32 ]. In this study, after five times of RF therapy (monopolar mode for 15 min, bipolar mode for another 10-minute), 69.61% patients showed improvement in vaginal laxity according to VLQ score at 12 month and 29.41% patients obtained FSFI score no less than 26.55 at 12 months, accompanying by the elevated SSQ score, indicating temperature controlled dual-mode (monopolar and bipolar) RF contributed to the alleviated vaginal laxity and increased sexual satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic quadripolar radiofrequency (DQRF) is a novel technique that is also rapidly gaining attention. A systematic review showed improvements in vulvovaginal aesthetics, sexual satisfaction and relief of symptoms caused by vulvovaginal atrophy ( Elbiss et al, 2022 ). All the studies to date have been conducted by people affiliated with the Novavision Group, the company behind DQRF.…”
Section: Evidencementioning
confidence: 99%